Angiotensin-converting enzyme activity in Cavalier King Charles Spaniels with an ACE gene polymorphism and myxomatous mitral valve disease. Issue 2 (February 2018) - Meurs, Kathryn M.; Olsen, Lisbeth H.; Reimann, Maria J.; Keene, Bruce W.; Atkins, Clarke E.; Adin, Darcy; Aona, Brent; Condit, Julia; DeFrancesco, Teresa; Reina-Doreste, Yamir; Stern, Joshua A.; Tou, Sandra; et al.
Abstract : Objectives: Myxomatous mitral valve disease (MMVD) is the most common heart disease in the dog. It is particularly common in the Cavalier King Charles Spaniel (CKCS) breed and affected dogs are frequently managed with angiotensin-converting enzyme inhibitors (ACE-I). We have previously identified a canine ACE gene polymorphism associated with a decrease in angiotensin-converting enzyme (ACE) activity. The aim of this study was to evaluate for the prevalence of the ACE polymorphism in CKCS with mitral valve disease and to determine whether the presence of the polymorphism is associated with alterations in ACE activity at different stages of cardiac disease. Methods: Seventy-three dogs with a diagnosis of mitral valve disease were evaluated and a blood sample was drawn for ACE polymorphism genotyping and ACE activity measurement. Results: Forty-three dogs were homozygous for the ACE polymorphism; five were heterozygous and 25 were homozygous wild type. The mean age and the median severity of disease were not different for dogs with the polymorphism and dogs with the wild-type sequence. The median baseline ACE activity was significantly lower for the ACE polymorphism (27.0 U/l) than the wild-type sequence dogs (31.0 U/l) ( P =0.02). Dogs with more severe disease and the ACE polymorphism had significantly lower levels of ACE activity than dogs with the wild-type sequence ( P =0.03). Conclusion: The CKCS appears to have a high prevalence of the ACE variant. Dogs with the ACE variant had lower levels of ACE activity even in more advanced mitral valve disease than dogs without the variant. The clinical significance of this finding and its impact on the need for ACE-I in dogs with the polymorphism and heart disease deserves further study.